Air quality and adverse health effects of personnel exposed to airborne contaminants at Child Development Centres, Phatthalung Province, Thailand - Decharat, Somsiri; Phethuayluk, Piriyalux (YCAB Publisher, 2025)
Background: Indoor air quality (IAQ) is a critical factor influencing public health, especially in environments inhabited by vulnerable populations such as young children. Child Development Centres (CDCs) are particularly at risk of harboring airborne biological contaminants such as bacteria and fungi, which are affected by environmental variables including temperature and humidity. These contaminants can contribute to respiratory issues and other health complications. Objective: This study aimed to assess the levels of indoor temperature and relative humidity, evaluate bacterial and fungal concentrations, examine perceived health risks, and analyze the association between environmental parameters and microbial load in CDCs in Phatthalung Province, Thailand. Methods: A cross-sectional study was conducted at 20 CDCs from 1 to 27 February 2022, involving 59 staff members. Microbial air sampling was performed using settle plates based on gravitational sedimentation. Temperature and humidity were recorded at 8:30–9:30 AM and 2:30–3:30 PM. A structured questionnaire was used to assess health risk perceptions. Data were analyzed using descriptive and comparative statistics (p < 0.05). Results: Average temperatures were 24.51 ± 0.59°C and 25.03 ± 0.63°C, while relative humidity levels were 56.40 ± 5.08% and 56.30 ± 5.08%, respectively. Microbial loads met acceptable standards, yet significant differences were observed based on ventilation, cleaning frequency, number of children, and time of sampling. Over half of respondents recognized health risks from poor IAQ. Conclusion: While microbial concentrations were within acceptable limits, regular monitoring and effective ventilation systems remain essential to minimize potential health risks in CDCs. Keywords: bacteria; fungi; indoor air quality; perceived health risks; childcare centres